Convergence of the Point Vortex Methods for Euler Equation on Half Plane (Journal of Computational Mathematics, 1996)
In this paper, we study the point vortex method for 2-D Euler equation of incompressible flow on the half plane, and the explicit Euler's scheme is considered with the reflection method handling the boundary condition. Optimal error bounds for this fully discrete scheme are obtained.